Calcium Administration Is Associated with Adverse Outcomes in Critically Ill Patients Receiving Parenteral Nutrition: Results from a Natural Experiment Created by a Calcium Gluconate Shortage. Issue 11 (1st November 2016) - Dotson, Bryan; Larabell, Patrick; Patel, Jasmine U.; Wong, Kristoffer; Qasem, Lina; Arthur, William; Leiberman, Chaim; Whittaker, Peter; Tennenberg, Steven D.
Abstract : Study Objective: Parenteral calcium is frequently administered to critically ill patients. However, animal studies demonstrate that calcium administration during critical illness heightens inflammation and leads to shock, organ dysfunction, and mortality. We sought to evaluate the association between calcium administration and adverse outcomes in critically ill patients receiving parenteral nutrition (PN). Design: Retrospective cohort examined before and during a calcium gluconate shortage. During the shortage, calcium was absent from PN, but calcium supplementation outside of PN was allowed. The shortage resulted in a natural experiment that included a group of patients who did not receive calcium. Setting: Intensive care units (ICUs) in three teaching hospitals. Patients: A total of 259 adults who received PN in the ICU for 48 hours or longer. Measurements and Main Results: Patients were divided into quartiles based on amount of parenteral calcium received; the lowest quartile received no calcium. End points were in‐hospital mortality, acute respiratory failure, new‐onset shock, and a composite of any one of these end points. For patients not on mechanical ventilation or vasoactive support when PN started, logistic regression revealed that calcium administration was associated with mortality (odds ratio [OR] 2.48, 95% confidence interval [CI] 1.08–5.69), acute respiratory failure (OR 2.43, 95% CI 1.28–4.60), new‐onset shock (OR 2.81, 95% CI 1.22–6.44), and the combined end point (OR 2.33, 95% CI 1.31–4.16). The odds of adverse outcomes increased as the calcium dose increased. Conclusion: Calcium administration correlated with adverse outcomes in critically ill patients receiving PN. The data suggest that administration of parenteral calcium to critically ill patients may be harmful.